EMIMBF4–GBL binary electrolyte working at −70 °C and 3.7 V for a high performance graphene-based capacitor. Issue 8 (6th February 2018) - Tian, Jiarui; Cui, Chaojie; Xie, Qing; Qian, Weizhong; Xue, Chi; Miao, Yonghua; Jin, Ying; Zhang, Gang; Guo, Baohua
Abstract : Addition of GBL in EMIMBF4 contributes to high capacitance performance of EDLC at −70 °C. Abstract : Developing an ionic-liquid (IL) type electrolyte with both high voltage window and wide temperature window, especially the low temperature range, is crucial to increase the energy density of the associated electrical double layer capacitors. We proposed the addition of γ-butyrolactone (GBL) in EMIMBF4 to form a binary electrolyte. The melting point (∼15 °C) of EMIMBF4 disappeared and the glass transition point decreased from −95 °C (for pure EMIMBF4 ) to −126 °C for the binary electrolyte. The binary electrolyte also exhibited improved ionic conductivity (26 and 0.31 mS cm −1 at 20 and −70 °C, respectively) and allowed an electrode of mesoporous graphene to exhibit a capacitance of 131 F g −1 and energy density of 61 W h kg −1 at −70 °C and 3.7 V, the highest values reported so far. NMR and ATR-IR characterization validated the strong interaction between GBL and EMIMBF4 for breaking the ion pairs of the latter but without forming the solvated ions, as in the system of EMMIBF4 with propylene carbonate.